Theoretical design of novel PdZn alloy catalysts for methanol steam reforming : hydrogen product for fuel cell - Lim, Kok Hwa. (2012)
Increasing regulations on the emission of air pollutants have stimulated interest in fuel cells, which use hydrogen as energy source, in particular for vehicles. One strategy of hydrogen production relies on an efficient in situ conversion of methanol to hydrogen. A typical process for this purpose is methanol steam reforming, CH3OH + H2O → H2 + CO2. Recently, the novel Pd/ZnO catalyst has been found to have an activity and selectivity for methanol steam reforming comparable to that of Cu/ZnO, the commonly used catalyst for this reaction. It exhibits good thermal stability more superior than the Cu based catalysts. However, detailed understanding of the elementary reaction steps of